2016
DOI: 10.21746/ijbio.2016.03.0014
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequency of Cytomegalovirus (CMV) in Tissue Samples of Women with Breast Cancer in Sanandaj, Iran.

Abstract: Despite the researchers’ efforts, the cause and development of breast cancer is still incompletely understood. Currently, in some reports, human cytomegalovirus has been referred as a risk factor for breast cancer. This study aimed to determine relative frequency of cytomegalovirus in tissue samples of women with breast cancer in Sanandaj County. In this study, to determine the relative frequency of the human cytomegalovirus (CMV) 50 formalin-fixed tissues of breast cancer, which all were invasive ductal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…On the other hand, among the 35 control group samples (fibroadenoma), 10 (28.57%) cases were positive for HCMV DNA (P >0.028.). In accordance to our findings, (Karimi et al, 2016) detected HCMV DNA in 26/50 (58%) samples of invasive breast carcinoma by using the nested-PCR method in Sanandaj city, Iran. Taher et al, (2013) from Sweden demonstrated HCMV IE protein expression in 100% of 73 breast cancer samples using the IHC method and real-time PCR.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, among the 35 control group samples (fibroadenoma), 10 (28.57%) cases were positive for HCMV DNA (P >0.028.). In accordance to our findings, (Karimi et al, 2016) detected HCMV DNA in 26/50 (58%) samples of invasive breast carcinoma by using the nested-PCR method in Sanandaj city, Iran. Taher et al, (2013) from Sweden demonstrated HCMV IE protein expression in 100% of 73 breast cancer samples using the IHC method and real-time PCR.…”
Section: Resultssupporting
confidence: 90%
“…[ 21 ] also reported a significant association between HCMV and breast cancer, with higher serum levels of HCMV IgG in 82% of 28 patients with inflammatory breast carcinoma compared to 65% of 49 patients with non-inflammatory breast carcinoma. Karimi et al [ 22 ] from Iran also detected HCMV DNA in 26 of the 50 samples (58%) of invasive breast carcinoma by using the nested-PCR method in Sanandaj city, Kurdistan Province. Perhaps the different prevalence of HCMV in various geographical areas in Iran may justify the different findings of the Karimi et al study and ours.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies succeeded to show relationship between HCMV and breast cancer. For example, Harkins et al [ 24] in the United States demonstrated a higher expression of HCMV antigens in breast cancer compared to normal breast epithelium (97% versus 63%), and Karimi et al [ 25] also detected HCMV DNA in 26 of the 50 samples (58%) of invasive breast carcinoma by using the nested-PCR method in Iran. The differed prevalence of EBV and HCMV in various geographical areas may justify the different findings of studies Moreover, the different fixation times of tissue samples in various centers,, and time of exposure to the virus in life (early or late) may also justify some differences in the research findings.…”
Section: Discussionmentioning
confidence: 99%